Lacrimal gland development: From signaling interactions to regenerative medicine. Issue 12 (18th August 2017) - Garg, Ankur; Zhang, Xin
Abstract : The lacrimal gland plays a pivotal role in keeping the ocular surface lubricated, and protecting it from environmental exposure and insult. Dysfunction of the lacrimal gland results in deficiency of the aqueous component of the tear film, which can cause dryness of the ocular surface, also known as the aqueous‐deficient dry eye disease. Left untreated, this disease can lead to significant morbidity, including frequent eye infections, corneal ulcerations, and vision loss. Current therapies do not treat the underlying deficiency of the lacrimal gland, but merely provide symptomatic relief. To develop more sustainable and physiological therapies, such as in vivo lacrimal gland regeneration or bioengineered lacrimal gland implants, a thorough understanding of lacrimal gland development at the molecular level is of paramount importance. Based on the structural and functional similarities between rodent and human eye development, extensive studies have been undertaken to investigate the signaling and transcriptional mechanisms of lacrimal gland development using mouse as a model system. In this review, we describe the current understanding of the extrinsic signaling interactions and the intrinsic transcriptional network governing lacrimal gland morphogenesis, as well as recent advances in the field of regenerative medicine aimed at treating dry eye disease. Developmental Dynamics 246:970–980, 2017 . © 2017 Wiley Periodicals, Inc. Key Findings: Abnormalities of the lacrimal gland underlie aqueous‐deficient dry eye disease. FGF signaling is the key regulator of lacrimal gland morphogenesis. The adult lacrimal gland harbors intrinsic stem or progenitor cells. Developmental mechanisms can guide efforts in lacrimal gland regeneration.